Effects of Sulphur on Growth and Yield of Soybean, Glycine max - Morshed, RM; Rahman, MM; Rahman, MA (Journal of Bangladesh Academy of Sciences, 2010)
DOI: 10.3329/jbas.v33i2.4108 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 235-237, 2009